Pelatihan Pembukuan Kelompok Wanita Tani (KWT) Karya Bunda - Nugraeni; Indah Susilawati (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2020)
The Women Farmers Group (KWT) is a group of mothers in order to advance agriculture, especially the management of agricultural products, economic growth and community welfare (eradicating poverty, overcoming unemployment), social and cultural development. KWT Karya Bunda is located in Patukan, Ambarketawang, Gamping, Sleman Yogyakarta, within 7.5 KM from Mercu Buana University Yogyakarta. This KWT has a strategic location which is close to the Vegetable and Fruit Main Market. This PKM helps the problem of managing KWT, namely bookkeeping and online promotion. The method used is online training and mentoring and promotion. The result of the PKM is an increase in knowledge about preparing financial statements (balance sheets, reports of changes in capital and profit and loss reports) i. So you can find out how many assets and where these assets come from, can arrange cash flow for the future. With online promotion there is an increase in income